Postural control in high-level kata and kumite karatekas - Gauchard, G. C.; Lion, A.; Bento, L.; Perrin, P. P.; Ceyte, H. (Movement & Sport Sciences - Science & Motricité, 2018)
Postural performance may vary according to the constraints related to the practice of different martial arts. This study aimed to investigate the visual and tactile contribution in balance control: (i) between karatekas and sedentary controls; (ii) between kata and kumite specialists within the elite karatekas. Balance control in quiet stance of 23 high-level karatekas (11 kata and 12 kumite specialists) and of 24 sedentary controls was evaluated in four sensory context conditions, a combination of visual cue availability (eyes open or closed) and tactile support reliability (firm or foam surface). The results showed that karatekas had a reduced body sway and a smaller sway area compared to controls, especially in the more challenging condition, i.e. eyes closed on a foam surface. Moreover, kata karatekas tended to have a reduced body sway and a smaller sway area than kumite karatekas in all sensory conditions. The practice of karate may enhance balance control in quiet stance by optimizing the role of tactile cues and by decreasing the weighting of visual cues. Moreover, the specialization into different karateka practices may induce the implementation of specific postural strategies to solve a given balance problem.